Produksi Maltodekstrin Secara Enzimatik dengan Menggunakan Berbagai Massa Pati Biji Durian (Durio zibethinus Murr.) - Ayu Satmah; Nurhaeni Nurhaeni; Jaya Hardi; Indriani Indriani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Durian seeds (Durio zibethinus Murr.) are one part of the durian fruit which has a high carbohydrate content so that it is a potential source of maltodextrin. The production of maltodextrin from durian seed starch has been carried out using the Î±-amylase enzyme. This study aims to determine the mass of durian seed starch substrate required to produce maltodextrin with the best yield and value of Dextrose Equivalent (DE). Starch with masses of 5, 10, 15, 20, and 25 grams suspended in CaCl2 was hydrolyzed with Î±-amylase for 90 minutes. The results showed that the best mass of durian starch was 15 grams with a maltodextrin yield of 25.842% and a DE value of 11.493. Maltodextrin from durian seed starch has the potential to be developed because it has met the requirements of DE <20.